2022
DOI: 10.1038/s41562-021-01255-w
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ psychosocial well-being one year after the outbreak of the COVID-19 pandemic in Norway

Abstract: The COVID-19 pandemic has dramatically restricted adolescents' lives. We used nationwide Norwegian survey data from 2014-2021 (N = 227,258; ages 13-18) to examine psychosocial outcomes in adolescents before and during the pandemic. Multilevel models revealed higher depressive symptoms and less optimistic future life expectations during the pandemic, even when accounting for the measures' time trends. Moreover, alcohol and cannabis use decreased, and screen time increased. However, the effect sizes of all obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
81
5
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 52 publications
4
81
5
4
Order By: Relevance
“…Preliminary evidence indicated that the pandemic has greater adverse effects on mental health among girls, younger adolescents, and adolescents with migrant backgrounds and low socio-economic status (SES) ( 15 18 ). A nationwide Norwegian study also confirmed that girls, younger adolescents, and adolescents with low parental education and from poor families showed greater adverse changes during the pandemic on mental health and social relationships than older adolescents ( 19 ). However, it is unknown whether these sociodemographic characteristics moderate the association between COVID-19 worries and adolescent mental health and life satisfaction.…”
Section: Introductionmentioning
confidence: 85%
“…Preliminary evidence indicated that the pandemic has greater adverse effects on mental health among girls, younger adolescents, and adolescents with migrant backgrounds and low socio-economic status (SES) ( 15 18 ). A nationwide Norwegian study also confirmed that girls, younger adolescents, and adolescents with low parental education and from poor families showed greater adverse changes during the pandemic on mental health and social relationships than older adolescents ( 19 ). However, it is unknown whether these sociodemographic characteristics moderate the association between COVID-19 worries and adolescent mental health and life satisfaction.…”
Section: Introductionmentioning
confidence: 85%
“…Parents’ must invest time and emotional resources to respond to their children’s needs, and job stressors can lead to an energy depletion that negatively impacts the parent-adolescent relationship (Hagelskamp & Hughes, 2016 ). The demands of parent-adolescent dynamics have increased during the COVID-19 pandemic, as parents struggle to balance their work while supporting their children’s autonomy and educational and mental health needs (von Soest et al, 2022 ; Wang et al, 2022 ). In the COVID-19 context, adolescents are at a lower risk of contagion than older populations (Lacomba-Trejo et al, 2020 ), but are at a higher risk of lower well-being and higher distress due to the interruption of their developmental tasks (Orellana & Orellana, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic also affected adolescents and young people negatively. Although the COVID-19 pandemic does not cause significant physical risk to teenagers [ 12 , 13 ], the fear of infection, financial constraints, and social isolation pose a threat to the mental health of many adolescents [ 14 ]. The number of adolescents using e-cigarettes and smoking cigarettes decreased during the pandemic because of several reasons, including the presence of parents in the home, poor access to cigarette products during the pandemic, and concerns about increased risk of COVID-19 [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%